Meningkatkan Hasil Belajar Teknik Dasar Lay-Up Shoot Pada Permainan Bola Basket Melalui Metode Latihan Pada Siswa Kelas VIII 3 SMP Negeri 15 Ambon - Anaktototy, Y.; Divinubun, Siti; Woretma, Nurhalizah (Jurnal Ilmiah Wahana Pendidikan, 2026)
The purpose of this study is to improve the learning outcomes of lay-up shots in basketball through training methods for eighth-grade students of SMP Negeri 15 Ambon. The research method used in this study is classroom action research. The subjects of this study were 25 eighth-grade students of SMP Negeri 15 Ambon. After processing and analyzing the data, the results of cycle I, based on the cycle I learning outcomes table above, showed that 17 students had completed the practice (68%). Meanwhile, 8 students had not completed the practice (32%). In cycle II, based on the recapitulation table of student learning completeness in cycle II above, there were 25 students who completed the practice (100%) and no students who did not complete the practice (0%). From the results of data analysis and calculations, it can be concluded that the application of training methods in learning the basic techniques of Lay-Up Shoots in basketball can improve student learning outcomes. .